2021
DOI: 10.3389/fped.2021.656215
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Poor Prognosis of Severe Infection in Children With Idiopathic Nephrotic Syndrome: A Double-Center, Retrospective Study

Abstract: Background: Infection is the most common complication of Idiopathic Nephrotic Syndrome (INS) and the main cause of INS recurrence, severe infection and even leading to mortality. The purpose of this study was to investigate the risk factors of severe infection in INS children and the clinical parameters influencing prognosis.Methods: Totally 147 children with INS and concomitant infections were enrolled and classified into the severe infection group (SIG) and Non-severe infection group (Non-SIG). The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In the present study the most common complication observed during follow-up was URTIs (37%). Similarly, other studies report that acute respiratory tract infection is the most common infection [8]. In terms of the frequency of complications in the present study URTIs were followed by pneumonia, chickenpox, peritonitis, gastroenteritis, UTI, cellulitis, bacteremia, and hepatitis B infection.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study the most common complication observed during follow-up was URTIs (37%). Similarly, other studies report that acute respiratory tract infection is the most common infection [8]. In terms of the frequency of complications in the present study URTIs were followed by pneumonia, chickenpox, peritonitis, gastroenteritis, UTI, cellulitis, bacteremia, and hepatitis B infection.…”
Section: Discussionsupporting
confidence: 83%
“…Results from the present study are generally consistent with the existing literature describing the epidemiology of infections among patients with nephrotic syndrome, most notably, that steroids confer an increased risk of severe infection in adults and children with nephrotic syndrome when used alone or in combination with other immunosuppressive medications. 32 , 33 , 34 An analysis of steroid-associated side effects identified in electronic medical records from 884 adults and children with primary proteinuric kidney disease found a 2-fold increased risk of infection in those treated with corticosteroids. 35 The rate of severe infections in this cohort was 4.61 infections per 100 person-years, a finding similar to the rate in our study (6.1 infections/100 person-years).…”
Section: Discussionmentioning
confidence: 99%
“…Bệnh nhi với sang thương tối thiểu đáp ứng rất tốt với corticoidvốn là phương thức điều trị chính của HCTH, nhưng 75% trường hợp sẽ tái phát sau đó và 50% số ca bệnh sẽ diễn tiến đến tình trạng tái phát thường xuyên và lệ thuộc corticoid. Chính điều này sẽ dẫn đến việc sử dụng corticoid lâu dài, thậm chí cần phải kết hợp thêm những nhóm thuốc ức chế miễn dịch khác [3][4][5] .…”
Section: Tổng Quan Về Hội Chứng Thận Hư ở Trẻ Emunclassified